What Can Conjoint Experiments Tell Us about Americans' Abortion Attitudes?. Issue 2 (March 2022) - Doherty, David
I report findings from a pair of conjoint experiments that presented respondents with a series of profiles of pregnant women and asked whether it should be possible for each to obtain a legal abortion. The profiles varied the reason for the abortion, gestational age, and demographic characteristics of the hypothetical woman. I find little evidence that women's demographic characteristics—including their purported ethnoracial identities—affect these judgments. In contrast, the effects of gestational age and the reason for the abortion are substantial. Notably, the effects of gestational age appear to be linear and unresponsive to trimester and viability thresholds commonly cited in elite discourse. I also find that the reason for the abortion becomes more consequential as gestational age increases. Finally, I consider whether these effects vary with respondents' party affiliation and gender. The findings offer new insights into the contours of abortion attitudes in the United States and illustrate the strengths and limitations of conjoint designs.